Weak Efficiency of the Indonesian Share Market: Tests with Daily Data, 1983-1992 - Groenewold, Nicolaas; Ariff, Mohamed (Accounting Department,, 1995)
This paper sets out test of the weak Efficient Markets Hypothesis (EMH) and applies them to daily data for the Indonesian share market. Test used include traditional tests based on regression and correlation procedure as well as more recent test for the non-stationarity implications of the random-walk hypothesis, viz, the unit-root test and the variance -ratio test. Results are assessed for sensitivity with respect to October 1987 Crash. There is evidence of predictability in the share-price index, violating the weak EMH. Conclusions are not greatly affected by the omission of observations for October 1987 indicating that Indonesia was relatively isolated from the effects of the Crash.